Rancang Bangun Sistem Monitoring Dan Pemberi Pakan Otomatis Ayam Anakan Berbasis Internet Of Things (IoT) - Indra Gunawan; Hamzan Ahmadi; Muhammad Ramdani Said (Infotek: Jurnal Informatika dan Teknologi, 2021)
Farm is one of the largest food suppliers after agriculture. Many of the breeders do everything to improve the quality of their livestock. The usual way used by chicken farmers are by manual means such as temperature checking, and checking the availability of feed. Therefore it is necessary to create an automatic temperature monitoring and chicken feeding tool, which in this research  based on IoTs (Internet of Things). It uses DHT11 sensors to measure temperature in cages, Arduino Uno and NodeMCU ESP 8266 as microcontrollers and blynk applications as temperature monitoring tools. It consists of several interconnected parts. Starting from the DHT11 sensor measuring the temperature, then sent to the microcontroller after it is processed, then sent to the blynk webserver so that it can be accessed and displayed by the monitoring application. While chicken feeding can be made easier using servo motor as a door feeder chicken that works with scheduling system, then for the availability of feed will be measured by the specified weight. If the weight reaches a number less than or equal to 400 grams, then the loadcell sensor will send a notification to blynk with the message . The result of this researchs can monitor the temperature in the cage and provide feed automatically even though it  still not maximal.